Carbazole‐Based Tetrapodal Anchor Groups for Gold Surfaces: Synthesis and Conductance Properties. Issue 2 (27th November 2019) - O'Driscoll, Luke J.; Wang, Xintai; Jay, Michael; Batsanov, Andrei S.; Sadeghi, Hatef; Lambert, Colin J.; Robinson, Benjamin J.; Bryce, Martin R.
Abstract: As the field of molecular‐scale electronics matures and the prospect of devices incorporating molecular wires becomes more feasible, it is necessary to progress from the simple anchor groups used in fundamental conductance studies to more elaborate anchors designed with device stability in mind. This study presents a series of oligo(phenylene‐ethynylene) wires with one tetrapodal anchor and a phenyl or pyridyl head group. The new anchors are designed to bind strongly to gold surfaces without disrupting the conductance pathway of the wires. Conductive probe atomic force microscopy (cAFM) was used to determine the conductance of self‐assembled monolayers (SAMs) of the wires in Au–SAM–Pt and Au–SAM–graphene junctions, from which the conductance per molecule was derived. For tolane‐type wires, mean conductances per molecule of up to 10 −4.37  G0 (Pt) and 10 −3.78  G0 (graphene) were measured, despite limited electronic coupling to the Au electrode, demonstrating the potential of this approach. Computational studies of the surface binding geometry and transport properties rationalise and support the experimental results. Abstract : Four‐legged friends : Self‐assembled monolayers of molecular wires with new anchoring units containing four thiomethyl groups were formed on gold and their conductance was measured. The tetrapodal anchors provide effective binding but contribute minimally to the conductance pathway of the wires. Surface binding and electronic coupling can therefore be considered independently.